Town House : Architecture and Material Life in the Early American City, 1780-1830 - Herman, Bernard L., 1951- (Book collections on Project MUSE., 2005)
In this abundantly illustrated volume, Bernard Herman provides a history of urban dwellings and the people who built and lived in them in early America. In the eighteenth century, cities were constant objects of idealization, often viewed as the outward manifestations of an organized, civil society. As the physical objects that composed the largest portion of urban settings, town houses contained and signified different aspects of city life, argues Herman. Taking a material culture approach, Herman examines urban domestic buildings from Charleston, South Carolina, to Portsmouth, New Hampshire, as well as those in English cities and towns, to better understand why people built the houses they did and how their homes informed everyday city life. Working with buildings and documentary sources as diverse as court cases and recipes, Herman interprets town houses as lived experience. Chapters consider an array of domestic spaces, including the merchant family's house, the servant's quarter, and the widow's dower. Herman demonstrates that city houses served as sites of power as well as complex and often conflicted artifacts mapping the everyday negotiations of social identity and the display of sociability.